Molecular and serological detection of Anaplasma spp. in small ruminants in an area of Cerrado Biome in northeastern Brazil - Silva, Ellainy Maria Conceição (2024)
Anaplasmosis, caused by bacteria of the genus Anaplasma, is an important tick-borne disease that causes economic losses to livestock farms in many countries. Even though Anaplasma spp. have been detected in goats and sheep worldwide, few studies investigate the occurrence and genetic identity of these agents in small ruminants from Brazil. Thus, this work aimed to detect and determine the genetic identity of Anaplasma spp. in small ruminants from the Baixo Parnaíba region, state of Maranhão, northeastern Brazil. For this purpose, blood samples were collected from 161 animals (91 goats; 70 sheep) from 4 municipalities in the Baixo Parnaíba region. Sheep and goat serum samples were subjected to recombinant membrane surface protein (MSP5)-based iELISA. Whole blood samples were subject to DNA extraction and molecular diagnosis using PCR assays for Anaplasma spp. targeting msp1β, msp1α, 16S rRNA and msp4 genes. Positive samples were sequenced and then subjected to Anaplasma marginale msp1α genetic diversity analysis and phylogenetic inferences based on the 16S rRNA and msp4 genes. The serological survey detected the presence of anti-A. marginale IgG antibodies in 18 animals (11.1%): 2.9% (2/70) sheep and 17.4% (16/91) goats. Anaplasma marginale DNA was detected in 2 goats (1.2%) using qPCR based on the msp1β gene. Two distinct A. marginale msp1α strains, namely α β and α β ΓγΓγΓγΓγ were found in the infected goats, each one found in a different animal, both belonging to the H genotype. Phylogenetic analysis based on the 16S rRNA gene showed the sequences positioned in three different clades and grouped with sequences from ‘Candidatus Anaplasma boleense’, A. platys and A. marginale. Phylogenetic inferences based on the msp4 gene positioned the sequence variants in the A. marginale clade. The present work represents the first molecular detection of sequence variants phylogenetic associated to ‘Candidatus Anaplasma boleense’ and A. platys and α β and α β ΓγΓγΓγΓγ in goats from Brazil.